2004
DOI: 10.1159/000077516
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal aberrations in arsenic-exposed human populations: a review with special reference to a comprehensive study in West Bengal, India

Abstract: For centuries arsenic has played an important role in science, technology, and medicine. Arsenic for its environmental pervasiveness has gained unexpected entrance to the human body through food, water and air, thereby posing a great threat to public health due to its toxic effect and carcinogenicity. Thus, in modern scenario arsenic is synonymous with “toxic” and is documented as a paradoxical human carcinogen, although its mechanism of induction of neoplasia remains elusive. To assess the risk from environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 21 publications
(18 reference statements)
1
13
0
Order By: Relevance
“…The results of the present study showed that arsenic exposure caused genotoxicity in plant cells, which is consistent with the earlier reports in a variety of cultured human cells [33][34][35], animals [16,36], and arsenic-exposed human populations [37,38].…”
Section: Fig 3 Mitotic Index Insupporting
confidence: 93%
“…The results of the present study showed that arsenic exposure caused genotoxicity in plant cells, which is consistent with the earlier reports in a variety of cultured human cells [33][34][35], animals [16,36], and arsenic-exposed human populations [37,38].…”
Section: Fig 3 Mitotic Index Insupporting
confidence: 93%
“…This could then explain the increased level of chromosomal aberrations seen in As[III] exposed individuals. Indeed some reports suggest that the level of chromosomal damage in exposed individuals can be used to predict future risk of cancer (64). …”
Section: Discussionmentioning
confidence: 99%
“…Arsenic contamination has reached an alarming proportion in various districts of West Bengal, an eastern state of India, and in Bangladesh, so much so that it has been earmarked as bthe biggest arsenic calamity in the worldQ [1][2][3][4]. A large number of people from this area are endemically exposed to arsenic-contaminated groundwater due to drinking of tube well water containing arsenic level above World Health Organization's maximum permissible limit of 50 Ag/L [5].…”
Section: Introductionmentioning
confidence: 99%